2012
DOI: 10.1161/circulationaha.111.069518
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Catecholamine Stress on Diastolic Function and Myocardial Energetics in Obesity

Abstract: Background-Obesity is characterized by impaired cardiac energetics, which may play a role in the development of diastolic dysfunction and inappropriate shortness of breath. We assessed whether, in obesity, derangement of energetics and diastolic function is further altered during acute cardiac stress. Methods and Results-Normal-weight (body mass index, 22Ϯ2 kg/m 2 ; nϭ9 -17) and obese (body mass index, 39Ϯ7 kg/m 2 ; nϭ17-46) subjects underwent assessment of diastolic left ventricular function (cine magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(116 citation statements)
references
References 40 publications
3
110
2
1
Order By: Relevance
“…Furthermore, obesity, DMII and IR can have direct adverse effects on myocardial structure and function independently of common confounders as hypertension or coronary artery disease, which has been referred to as "obesity" [116], "diabetic" [117] or "insulin-resistant" [118] cardiomyopathy. Adverse myocardial structural and functional changes induced by obesity, DMII and IR include myocardial hypertrophy and fibrosis [119][120][121], reduced myocardial energetic reserve [122][123][124], impaired myocardial relaxation [115,125] and increased diastolic LV [72] and cardiomyocyte stiffness [126]. Metabolic risk factors are strongly associated with myocardial and systemic inflammation, oxidative stress and endothelial dysfunction [116][117][118], which importantly contribute to myocardial dysfunction and remodeling and result in downregulation of NO-cGMP-PKG signaling [127,128].…”
Section: Metabolic Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, obesity, DMII and IR can have direct adverse effects on myocardial structure and function independently of common confounders as hypertension or coronary artery disease, which has been referred to as "obesity" [116], "diabetic" [117] or "insulin-resistant" [118] cardiomyopathy. Adverse myocardial structural and functional changes induced by obesity, DMII and IR include myocardial hypertrophy and fibrosis [119][120][121], reduced myocardial energetic reserve [122][123][124], impaired myocardial relaxation [115,125] and increased diastolic LV [72] and cardiomyocyte stiffness [126]. Metabolic risk factors are strongly associated with myocardial and systemic inflammation, oxidative stress and endothelial dysfunction [116][117][118], which importantly contribute to myocardial dysfunction and remodeling and result in downregulation of NO-cGMP-PKG signaling [127,128].…”
Section: Metabolic Risk Factorsmentioning
confidence: 99%
“…Impaired myocardial relaxation results from obesity-induced myocardial mitochondrial dysfunction, lipotoxicity, uncoupled oxidative phosphorylation and disturbed cardiomyocyte calcium handling [135]. Compared to normal weight subjects, obese individuals had impaired myocardial energetics (phosphocreatine/ATP ratio) and diastolic filling rate at rest, which further deteriorated after inotropic stress [123]. Myocardial blood flow, as measured by PET, was significantly reduced in obese postmenopausal women, which was negatively correlated with waist/hip ratio [136].…”
Section: Overweight/obesitymentioning
confidence: 99%
“…23,29 It has been shown that in animal models of obesity 35 and in humans with no other co-morbidity, abnormally low PCr/ATP ratios occur at rest, potentially due to, in addition to changes in substrate utilization, a loss of the total creatine pool in proportion to the loss of PCr, as occurs in many other forms of hypertrophy. 1,[78][79][80][81] Furthermore, this has been linked to altered cardiac diastolic function and is exacerbated during catecholamine stress. 80 …”
Section: Cardiac Energetics and Obesitymentioning
confidence: 99%
“…1,[78][79][80][81] Furthermore, this has been linked to altered cardiac diastolic function and is exacerbated during catecholamine stress. 80 …”
Section: Cardiac Energetics and Obesitymentioning
confidence: 99%
See 1 more Smart Citation